New Global Interchange Formula of Parameter Conjugate gradient method for solving optimization - Mohammed, Lajan (Sulaimani Journal for Pure and Applied Sciences, 2025)
In this study, we develop a new hybrid conjugate gradient method designed to generate a descent search direction that is independent of line search, thereby ensuring global convergence. We introduce an innovative interchange formula for the parameter, which consistently produces a descent direction for the objective function at each iteration. Through extensive numerical experiments, we demonstrate that the proposed algorithm achieves global convergence, performing comparably to other leading algorithms in the field. The results highlight the robustness and efficiency of our method, making it a valuable tool for unconstrained optimization problems.
Keywords: unconstrained optimization; hybrid conjugate gradient method; inexact line search; global convergence